Adolescent opioid use: Examining the intersection of multiple inequalities. Issue 4 (2nd October 2019) - Bares, Cristina B.; Weaver, Addie; Kelso, Mary F.
Abstract: Nonmedical prescription opioid use in the U.S. has increased, with devastating consequences. Yet, we know little about how multiple inequalities impact adolescent opioid use. Using data from the 2015 Monitoring the Future study, we address this gap by examining adolescent opioid use by residential context, parental education, across race/ethnicity and sex. Bivariate findings demonstrate differential patterns of use by residential context and SES across race/ethnicity and sex. Multi-group logistic regression analyses were used to explore whether associations in parental education, residential context, sex with opioid use differed within race/ethnicity. Our results suggest that intersecting identities lead to different rates of opioid use among adolescents and that multiple identities should be considered when designing treatment interventions for adolescent opioid use. Findings also reveal a need to acknowledge racial/ethnic heterogeneity among rural adolescents and how the rural context relates to opioid use. Implications for community-based approaches for addressing these inequalities are addressed.